Advanced epoxy composites for tribological Applications: Investigating the role of hybrid ceramic and lubricant fillers - Ratchagaraja Dhairiyasamy; Welson Bassi; Abdullah A. Algethami; Bahaa Saleh; Sivakumar Jaganathan; Deekshant Varshney; Subhav Singh (Polymer Testing, 2025)
Epoxy resins are widely employed in structural and industrial applications due to their high strength and chemical resistance, but their poor tribological performance under dynamic loading conditions limits their use in high-friction environments. Enhancing these properties through the use of functional fillers presents a promising approach; however, the combined effects of reinforcing and lubricating agents within epoxy remain underexplored. This study aims to evaluate the tribological and thermal performance of epoxy composites reinforced with silicon carbide (SiC), graphite (Gr), and molybdenum disulfide (MoS2), both individually and in hybrid combinations. Eight composite formulations were prepared via mechanical stirring, ultrasonication, and compression molding, and were subjected to pin-on-disc testing under varying normal loads and sliding speeds. The composites were characterized in terms of coefficient of friction (COF), specific wear rate, and interfacial temperature rise, alongside SEM and EDX analysis of the worn surfaces. Results revealed that SiC improved wear resistance, while Gr and MoS2 reduced COF and surface heating. The ternary composite (EP + SiC + Gr + MoS2) demonstrated the best overall performance, with a 94 % wear reduction and 40 % lower COF compared to pure epoxy. These findings confirm the synergistic benefit of combining reinforcing and lubricating fillers in polymer composites. Future studies should explore long-term performance and applicability under real operating conditions.